COMPLEX HISTOLOGICAL AND IMMUNOHISTOCHEMICAL STUDY OF MONOCYTOPOIESIS IN RATS WITH DETERMINATION OF PROLIFERATIVE ACTIVITY BY EXPRESSION KI67 AND CD68+ IN THE EXPERIMENT - Martynenko, R.V.; Shepitko, V.I.; Stetsuk, Ye.V.; Boruta, N.V.; Yakushko, O.S.; Martynenko, V.B. (World of Medicine and Biology, 2021)
Ki67 is not only one of the markers of proliferation, but also an indirect determinant of the rate of cell division. CD68 is exploited as a valuable cytochemical marker to immunostain monocyte/macrophages in the histochemical analysis of inflamed tissues, tumor tissues, and other immunohistopathological applications. The purpose of the study was to determine the cell proliferation index of the monocytic line of red bone marrow using antibodies to CD68+ and Ki-67 in the control and intact groups of animals. There were established an equivalent degree of proliferative activity by progenitor cells with Ki-67 expression in the control and intact groups.